2014
DOI: 10.1080/03235408.2013.809897
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of some plants powder and extract in the management of Angoumois grain moth,Sitotroga cerealella(Olivier) [Lepidoptera: Gelechiidae] infesting stored wheat grains

Abstract: Powders and extracts prepared from part and products of four plants species indigenous to Nigeria were tested under laboratory condition at 28 ± 2°C and 75 ± 5% relative humidity for their insecticidal potential against Angoumois grain moth, Sitotroga cerealella. Adult S. cerealella were exposed to three concentrations at rate 0.5, 1 and 2 g of Capsicum frutescens, Cymbopogon citratus, Moringa oleifera and Anacardium occidentale powders and extracts at the rate of 1, 2 and 3%/ 20 g of wheat grains. Parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…The percentage inhibition rate of the untreated control was 0%. This result is consistent with the result reported by Ileke 58 , in which no adult emergence was observed in wheat grains treated with C. frutescens and A. occidentale extracts at all tested concentrations, and adult emergence was significantly higher (p < 0.05) in the control than in the treated wheat grains.…”
Section: Discussionsupporting
confidence: 93%
“…The percentage inhibition rate of the untreated control was 0%. This result is consistent with the result reported by Ileke 58 , in which no adult emergence was observed in wheat grains treated with C. frutescens and A. occidentale extracts at all tested concentrations, and adult emergence was significantly higher (p < 0.05) in the control than in the treated wheat grains.…”
Section: Discussionsupporting
confidence: 93%
“…The death of insect larvae as results of agro waste toxicity that might have led to inability of larval to completely cast off their exoskeleton during moulting remained linked to the posterior part of their abdomen which can affect larval and pupa survival as well as growth disruption (Oigiangbe et al 2010;Ileke 2014). The agro waste powders and extracts had effect on post-embryonic survival of this insect which resulted in prevention of adult emergence at different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…One gravid female moth can completely devoid 50 g of paddy within the next three generations in storage, if control is neglected (Cogburn et al 1975, Hossien et al 2018. The moth larvae are the most destructive stage; they enter the grains and feed voraciously on the endosperm which can lead to loss of viability as a result of tunnels made within the paddy (Khattak et al 1996;Tripathi et al 2000;Ileke 2014;Mahmood 2018). The management of pre and post-harvest pests of crops has been the major concern of entomologists all over the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…at 1 % w/w discouraged egg laying and larval mortality of S. cerealella; potentiality of this plant extract is due to the presence of sesquiterpenes, lactones (Ambrosio et al 2008). In another recent work, Ileke (2014) reported that powders and extracts of Capsicum frutescens L., Cymbopogon citratus DC. Stapf., Moringa oleifera Lamm.…”
Section: B Bioactivity Of Plant Extracts On Immature Stagesmentioning
confidence: 99%